Depressive symptoms and associated factors among adults attending antiretroviral therapy clinic in Debre Markos comprehensive specialized hospital, Amhara, Ethiopia - Haile Amha; Bethlehem Denekew; Sintayehu Asnakew (SAGE Open Medicine, 2022)
Objective: This study aimed to assess the prevalence and associated factors of depressive symptoms among adults attending anti-retroviral therapy follow up at Debre Markos Comprehensive Specialized Hospital. Methods: Institution-based cross-sectional study was conducted, and a systematic sampling technique was used to select the 266 participants. Depressive symptoms were assessed by using patient health questionnaire 9. A binary logistic regression analysis with an odds ratio and a 95% confidence interval was used to assess the strength of associations in SPSS version 20 and a p-value < 0.05 was considered as statistically significant. Results: In this study, the prevalence of depressive symptoms among HIV-positive individuals was 39.1% with 95% confidence interval (33.7%–45.3%). Multivariable analysis showed that participants who had age group > 40 (adjusted odds ratio = 5.26, 95% confidence interval (2.24–12.35)), presence of perceived stigma and discrimination (adjusted odds ratio = 7.5, 95% confidence interval = (3.77–14.9)), poor medication adherence (adjusted odds ratio = 6.05, 95% confidence interval = (2.86–12.80)), and poor social support (adjusted odds ratio = 2.53, 95% confidence interval = (1.25–5.12)) were significantly associated with depression. Conclusion: The prevalence of depressive symptoms in this study was found to be significantly high. Age > 40 years old, the presence of perceived stigma and discrimination, poor medication adherence, and a lack of social support were found to be associated factors of depressive symptoms. It would be better for clinicians to give special emphasis to those patients who were stigmatized, who had compliance problems, and poor social support.